Evolución del concepto de innovación y sus implicaciones en el sector hotelero: revisión de la literatura - Marleny Cardona Acevedo; Maribel Reinel Defelipe; Ilver Franc Serpa Ávila; Suelen Castiblanco M (Suma de Negocios, 2013)
The concept of economic development has been linked to the change in terms of improving processes and products, which result in a positive impact on the results. Somewhat, it’s a way of thinking about innovation. Although this concept is born and evolves mainly for the manufacturing sector, has come to be applied to services, where hotels are an important group. In these, it is important to prioritize the particularities of their activities for the purpose of considering the management of innovation. The studies reviewed here emphasize the role of human capital, business environment, the effect of the size of the hotel, customer orientation, among others. We conclude in them also there is a greater emphasis on incremental innovation (improvement in services and processes) that radical innovation (creating new services), as well as the acquisition of external technology to innovate above internal creation of innovation processes, reflected in the low investment in research and development -R & D.